Diffuse Optical Imaging V 2015
DOI: 10.1364/ecbo.2015.953813
|View full text |Cite
|
Sign up to set email alerts
|

Collagen content as a risk factor in breast cancer? A pilot clinical study.

Abstract: A retrospective pilot clinical study on time domain multi-wavelength (635 to 1060 nm) optical mammography was exploited to assess collagen as a breast-cancer risk factor on a total of 109 subjects (53 healthy and 56 with malignant lesions). An increased cancer occurrence is observed on the 15% subset of patients with higher age-matched collagen content. Further, a similar clustering based on the percentage breast density leads to a different set of patients, possibly indicating collagen as a new independent br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…This is because collagen quanti cation can be less accurate, due to the overall weak absorption of collagen and to the overlap of its absorption line shape with that of the strongly absorbing deoxyhemoglobin at short wavelengths and with that of lipids and water at long wavelength 31 . However, information on collagen content is of great interest since it is directly involved in the development of breast cancer and is itself a potential risk factor [40][41][42] Previous in vivo and ex vivo studies 32 have found that the scattering power b correlates with collagen and this is con rmed by our results (r = 0.844, p = 0.001). Thus, the Collagen Index (CI), that combines collagen concentration with the scattering power b, enhancing their correlation, could amplify their informative content.…”
Section: Estimate Of Breastsupporting
confidence: 77%
“…This is because collagen quanti cation can be less accurate, due to the overall weak absorption of collagen and to the overlap of its absorption line shape with that of the strongly absorbing deoxyhemoglobin at short wavelengths and with that of lipids and water at long wavelength 31 . However, information on collagen content is of great interest since it is directly involved in the development of breast cancer and is itself a potential risk factor [40][41][42] Previous in vivo and ex vivo studies 32 have found that the scattering power b correlates with collagen and this is con rmed by our results (r = 0.844, p = 0.001). Thus, the Collagen Index (CI), that combines collagen concentration with the scattering power b, enhancing their correlation, could amplify their informative content.…”
Section: Estimate Of Breastsupporting
confidence: 77%